Associations between long-term exposure to PM2.5 and site-specific cancer mortality: A nationwide study in Brazil between 2010 and 2018. (1st June 2022) - Yu, Pei; Xu, Rongbin; Li, Shanshan; Coelho, Micheline S.Z.S.; Saldiva, Paulo H.N.; Sim, Malcolm R.; Abramson, Michael J.; Guo, Yuming
Abstract: Long-term exposure to PM2.5 has been linked to lung cancer incidence and mortality, but limited evidence existed for other cancers. This study aimed to assess the association between PM2.5 on cancer specific mortality. An ecological study based on the cancer mortality data collected from 5, 565 Brazilian cities during 2010–2018 using a difference-in-differences approach with quasi-Poisson regression, was applied to examine PM2.5 -cancer mortality associations. Globally gridded annual average surface PM2.5 concentration was extracted and linked with the residential municipality of participants in this study. Sex, age stratified and exposure-response estimations were also conducted. Totalling 1, 768, 668 adult cancer deaths records of about 208 million population living across 5, 565 municipalities were included in this study. The average PM2.5 concentration was 7.63 μg/m 3 (standard deviation 3.32) with range from 2.95 μg/m 3 to 28.5 μg/m 3 . With each 10 μg/m 3 increase in three-year-average (current year and previous two years) concentrations of PM2.5, the relative risks (RR) of cancer mortality were 1.16 (95% confidence interval [CI]: 1.11–1.20) for all-site cancers. The PM2.5 exposure was significantly associated with several cancer-specific mortalities including oral, nasopharynx, oesophagus, and stomach, colon rectum, liver, gallbladder, larynx, lung, bone, skin, female breast, cervix, prostate, brain and leukaemia. No safe level of PM2.5 exposure was observed in the exposure-response curve for all types of cancer. In conclusion, with nationwide cancer death records in Brazil, we found that long-term exposure to ambient PM2.5 increased risks of mortality for many cancer types. Even low level PM2.5 concentrations had significant impacts on cancer mortality. Graphical abstract: Image 1 Highlights: Long-term exposure to ambient PM2.5 increased risks of mortality for many cancer types. There is no threshold for the effects of PM2.5 on mortality from all cancer sites. Even low level PM2.5 concentrations had significant impacts on cancer mortality.